MODEL OF MICROFINANCE FINANCING QUALITY DETERMINANTS BASED ON SOCIAL AND FINANCIAL ASPECTS: A CASE STUDY OF PT. PNM BOGOR AND ITS SURROUNDING AREAS (BOGOR CITY, BOGOR REGENCY, AND DEPOK) - Terminanto, Ade Ananto; Heirunissa, Heirunissa; Pratama, Yoghi Citra; Suherlan, Ade (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2025)
ABSTRACTThis study aims to analyze the influence of social and financial aspects on financing quality at PT PNM in the Bogor and Depok regions. The novelty of this research lies in its recommended social strategy for reducing Non-Performing Loan (NPL) levels. Using primary data from 106 respondents and secondary data, this study applies descriptive analysis methods and SEM-PLS. The results show that social aspects have a significant positive effect on financial aspects. Both social and financial aspects have been shown to have a significant negative effect on the potential for NPL. Social factors such as discipline, group solidarity (joint responsibility), and socio-economic stability of customers determine the smoothness of installments. Financially, the ability to manage business finances and effective risk management are key to maintaining portfolio quality. The study concludes that a strategy combining social and financial approaches is crucial for PT PNM to improve financial performance. It is recommended that PT PNM strengthen its mentoring program, customer education, and regular monitoring system for early risk detection. Mitigation strategies through the implementation of 3R (Rescheduling, Reconditioning, Restructuring) and intensive mentoring need to be optimized to adjust payment obligations to the real conditions of customers in the field.ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh aspek sosial dan keuangan terhadap kualitas pembiayaan di PT PNM wilayah Bogor dan Depok. Kebaruan penelitian ini terletak pada rekomendasi strategi aspek sosial untuk menekan tingkat Non-Performing Loan (NPL). Menggunakan data primer dari 106 responden serta data sekunder, penelitian ini menerapkan metode analisis deskriptif dan SEM-PLS. Hasil penelitian menunjukkan aspek sosial berpengaruh positif signifikan terhadap aspek keuangan. Baik aspek sosial maupun keuangan terbukti berpengaruh negatif signifikan terhadap potensi NPL. Faktor sosial seperti kedisiplinan, solidaritas kelompok (tanggung renteng), dan stabilitas sosial-ekonomi nasabah menjadi penentu kelancaran angsuran. Secara finansial, kemampuan pengelolaan keuangan usaha dan manajemen risiko yang efektif merupakan kunci menjaga kualitas portofolio. Penelitian menyimpulkan bahwa strategi kombinasi pendekatan sosial dan keuangan sangat krusial bagi PT PNM untuk meningkatkan kinerja keuangan. Disarankan agar PT PNM memperkuat program pendampingan, edukasi nasabah, serta sistem monitoring berkala untuk deteksi dini risiko. Strategi mitigasi melalui penerapan 3R (Rescheduling, Reconditioning, Restructuring) dan pendampingan intensif perlu dioptimalkan untuk menyesuaikan kewajiban pembayaran dengan kondisi riil nasabah di lapangan.